KAJIAN PENDIDIKAN AGAMA HINDU DALAM MENCERDASKAN KEHIDUPAN BANGSA INDONESIA - I Ketut Subagiasta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This paper explained about “The analysis education of Hindu in the intelligent of thelife nation of Indonesian”. As the prime explained of this writing namely about the effortsdevelopment education of Hindu, the hyndrance urgent dynamics the education of Hindu, therole any component in the education of Hindu, the social institution of Hindu for evore educationof Hindu, the seriousness for manage programme education of Hindu, and also about theincrease of the young people of the Hindu for study about education of the Hindu.